Museum Adityawarman sebagai Destinasi Wisata Edukasi dan Budaya di Kota Padang 2019-2024 - Rahmadia Rahmadia; Siti Fatimah (Lembaga Yasin AlSys, 2026)
Adityawarman Museum, as a government institution and an educational and cultural tourism destination in Padang City, has faced the dual challenges of the Covid-19 pandemic and increasing demands for modernized management, thereby requiring systematic transformation efforts. This study aimed to analyze the role and strengthening of Adityawarman Museum’s functions as an educational and cultural tourism destination in Padang City during the 2019–2024 period. The research employed a historical method comprising the stages of heuristics, source criticism, interpretation, and historiography. Data were obtained from museum archives, policy documents, activity reports, interviews, and field observations. The results show that the strengthening of Adityawarman Museum’s role and function as a tourism destination involves not only physical improvements but also enhanced institutional governance, updated exhibition design, collection development, the use of digital technology, and the development of educational and cultural programs. In the post-pandemic period, there has been an increase in museum visits as well as greater community participation. The study concludes that Adityawarman Museum has actively enhanced its functions and roles as a tourism destination, as evidenced by increased visitor numbers, the awarding of the Museum Lestari accolade in 2023, and its upgraded qualification to Type A Museum status in 2022, thereby reinforcing its position as a center of education, cultural preservation, and tourism.